Pengaruh Produk Domestik Bruto Sektor Industri dan Sektor Jasa terhadap Pertumbuhan Ekonomi Indonesia - Rayhan Witra Pratama; Syukron Saputra; Randa Gustiawan (CV. Doki Course and Training, 2026)
Abstract : This study aims to analyze the effect of Gross Domestic Product (GDP) from the industrial sector and the services sector on Indonesia’s economic growth over the period 2000–2024. The study uses secondary data obtained from official publications of Statistics Indonesia (BPS). The industrial sector represents the secondary sector, while the services sector represents the tertiary sector, both of which play a dominant role in the national economic structure. The analytical method employed is multiple linear regression using EViews 13 software. The dependent variable is the national economic growth rate, while the independent variables are GDP of the industrial sector and GDP of the services sector. The analysis examines both the simultaneous and partial effects of these sectors on economic growth and tests the significance of the relationships using t-tests, F-tests, and the coefficient of determination (R²), along with model validation through classical assumption tests. The results indicate that (1) GDP of the industrial sector and the services sector has a positive and significant effect on Indonesia’s economic growth. (2) The services sector shows a more dominant influence than the industrial sector, reflecting a structural shift toward a tertiary-based economy oriented toward productivity and innovation. The study concludes that increasing the contribution of the services sector alongside strengthening the industrial sector is simultaneously required to sustain national economic growth. Abstrak : Penelitian ini bertujuan untuk menganalisis pengaruh Produk Domestik Bruto (PDB) sektor industri dan sektor jasa terhadap pertumbuhan ekonomi Indonesia periode tahun 2000 hingga tahun 2024. Penelitian ini menggunakan data sekunder yang diperoleh dari publikasi resmi Badan Pusat Statistik (BPS). Sektor industri mewakili sektor sekunder, sedangkan sektor jasa mewakili sektor tersier yang masing-masing memiliki dominasi terhadap struktur ekonomi nasional. Metode analisis yang digunakan adalah regresi linier berganda dengan alat bantu perangkat lunak EViews 13. Variabel dependen dalam penelitian ini adalah laju pertumbuhan ekonomi nasional, sedangkan variabel independennya adalah nilai PDB sektor industri dan sektor jasa. Analisis dilakukan untuk mengetahui pengaruh simultan dan parsial dari kedua sektor terhadap pertumbuhan ekonomi serta menguji signifikansi hubungan antar variabel melalui uji t, uji F, dan koefisien determinasi (R²) serta validasi model dengan uji asumsi klasik. Hasil penelitian menunjukkan bahwa (1) PDB sektor industri dan sektor jasa berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi Indonesia. (2) Sektor jasa memiliki pengaruh yang lebih dominan dibandingkan sektor industri, mencerminkan pergeseran struktur ekonomi menuju sektor tersier yang berorientasi pada produktivitas dan inovasi. Penelitian ini menyimpulkan bahwa peningkatan kontribusi sektor jasa dan penguatan sektor industri secara simultan diperlukan untuk menjaga keberlanjutan pertumbuhan ekonomi nasional.